Factors Toward Risk Influencing Millennials Willingness to Invest in Peer-to-Peer Lending - Sisilia, Heng; Bustan, Stella Octaviani; Lestadi, Arief Kristianto; Gunadi, Willy (International Journal of Science and Society, 2024)
The objective of this study is to analyze the factors influencing the risk perception that affects millennials' willingness to invest in P2P lending. To achieve this goal, a conceptual model was developed involving variables such as financial literacy, company reputation, information security awareness, risk perception, and intention to invest. The sample consisted of 220 respondents, and data were collected through a questionnaire. Structural Equation Modeling and SmartPLS Statistical Software were used to examine the data. The study’s results suggest that, while financial literacy does not significantly affect risk perception, firm reputation and information security knowledge do. The findings also demonstrate that risk perception has a major impact on the intention to invest. The implications of this research highlight the importance of reputation and information security in shaping risk perception in the fintech sector. Fintech companies should prioritize building a strong reputation through good service, transparency, and authentic communication, as well as implementing robust cybersecurity measures to protect investor data. Financial practitioners also need to educate investors about risks and emphasize the importance of reputation and information security in decision-making, providing guidance in risk assessment and management aligned with investors' goals and risk tolerance.